Synthesis and Biological Evaluation of Oxazolone Derivatives - G Mariappan; Dipankar Sarkar; Rashmi Karki; Lipika Pandey; Deepak Kumar (Journal of Global Pharma Technology, 2010)
A new series of oxazolone derivatives (OXZ1 to OXZ5) were synthesized. The structures of the synthesized compounds were assigned on the basis of UV, IR, 1 H NMR and Mass spectral data. The synthesized compounds were screened for analgesic and anti-inflammatory activities. Among the entire test compounds OXZ1, OXZ2 and OXZ4 showed promising analgesic activity as compared to std. pentazocine. In case of anti-inflammatory activity, all the compounds are active. But OXZ2 was found to be more active as compared to std. aspirin. From both activities, the compound OXZ2 shows significantly more analgesic and anti-inflammatory activity. All the experimental results were statistically significant at p<0.01 level.